The Process of Producing Bioethanol from Delignified Cellulose Isolated from Plants of the Miscanthus Genus - Olga Kriger; Ekaterina Budenkova; Olga Babich; Stanislav Suhih; Nikolay Patyukov; Yakov Masyutin; Vyacheslav Dolganuk; Evgeny Chupakhin (Bioengineering, 2020)
Plants of the Miscanthus genus (Miscanthus Anderss.) have a unique index of biomass production in relation to the occupied area. Miscanthus plants can be attributed to promising second-generation raw materials for the production of bioethanol and biofuel. Miscanthus plants are characterized by a high cellulose content. Herein, we report the results of a study on the obtained delignified cellulose with subsequent processing into bioethanol using microbial communities. In the course of the study, the optimal conditions for the delignification of the initial plant material for cellulose were selected. Ethanol with a high degree of conversion was successfully obtained from the isolated delignified cellulose. The article describes the pilot technological scheme for the conversion of Miscanthus plant biomass to bioethanol involving the delignification stages, followed by the conversion of the resulting cellulose into bioethanol by a consortium of microorganisms. As a result of the study, it was found that delignification using trifluoroacetic acid leads to the production of cellulose of high purity. Bioethanol with a yield of 3.1% to 3.4% in terms of the initial amount of biomass was successfully obtained by a microorganism consortium of Saccharomyces cerevisiae M Y-4242/Pachysolen tannophilus Y-3269, and Scheffersomyces stipitis Y-3264.